Assessing Turkey's changing conflict management role after the Cold War: actorness, approaches and tools - PARLAR DAL, EMEL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2018)
This paper aims to shed light on Turkey's conflict management role after the Cold War using a three-layered framework consisting of the layers of actorness, approaches and tools. In doing so, it seeks to profile Turkey's international conflict management since the Cold War years with a special focus on the nature of its participation in conflict management as an active or passive actor, the perspectives from which it approaches conflict management, and the conflict management instruments it utilises. First, the paper will provide a conceptual framework of international conflict management based on the above-mentioned triad of actorness, approaches and tools as derived from the existing literature. Second, it will apply the selected three-layered analytical framework to Turkey to decipher its strengths and limitations in managing international conflicts.
Keywords: International conflict management; peacekeeping; mediation; peace enforcement; adjudication; Turkey; rising powers; TURKISH FOREIGN-POLICY; FALL; RISE